Dynamic disorder can explain non-exponential kinetics of fast protein mechanical unfolding - Costescu, Bogdan; Sturm, Sebastian; Gräter, Frauke (Journal of structural biology, 2017)
Protein unfolding often does not obey a simple two-state behavior. Previous single molecule force spectroscopy studies demonstrated stretched exponential kinetics of protein unfolding under a constant pulling force, the molecular origin of which remains subject to debate. We here set out to extensively sample the mechanical unfolding of ubiquitin and NuG2 by Molecular Dynamics (MD) simulations. Both proteins show kinetics best fit by stretched exponentials, with stretching exponents similar to those found in experiments, even though static disorder is absent in our short MD simulations. Instead, we can ascribe non-exponential kinetics to dynamic disorder, due to conformational fluctuations on the nanosecond timescale. Our study highlights the general role of dynamic disorder in protein kinetics on a broad range of time scales even including those probed in MD simulations.
Available online 19 October 2016
Gesehen am 02.10.2018